Rapid and accurate detection method for bluetongue virus based on CRISPR-Cas13a combined with RT-ERA - Zhou, Dong; Yu, Haibo; Shao, Yuntong; Gao, Caixia; Xia, Changyou; Qi, Yinglin (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionBluetongue virus (BTV), a vector-borne pathogen of domestic and wild ruminants, poses substantial global threats to livestock health and trade. Conventional detection methods, such as RT-qPCR, remain constrained by reliance on specialized equipment and prolonged turnaround times, limiting their utility in field settings.MethodsTo overcome these challenges, we developed an integrated isothermal amplification-CRISPR detection platform—Reverse Transcription-Enzymatic Recombinase Amplification coupled with CRISPR-Cas13a (RT-ERA/CRISPR-Cas13a)—enabling rapid, sensitive, specific and visual pan-serotype detection of BTV.ResultsThe assay demonstrated a sensitivity of 20 RNA copies/reaction within 55 min using three readout modalities: fluorescence values, visual fluorescence signals, and lateral flow test strips. Specificity evaluation revealed no cross-reactivity with 9 non-target pathogens, including epidemiologically significant viruses such as EHDV, AKAV, and CHUV. Clinical validation using 263 field samples demonstrated that RT-ERA/CRISPR-Cas13a achieved clinical sensitivities of 100%, 100%, and 96% with fluorescence values, fluorescence signals, and lateral flow strips, respectively, while maintaining 100% clinical specificity via all modalities. Field adaptation using Nucleic Acid Release Reagent (NARR) simplified crude sample processing, delivering 97% clinical sensitivity and 100% clinical specificity even in the presence of inhibitors from unpurified samples.ConclusionThis work represents the first CRISPR-Cas13a-based platform for pan-serotype BTV detection, combining portability, cost-efficiency, and detective accuracy suitable for point-of-care deployments. By bridging the gap between high laboratory sensitivity and practical field applicability, this system enables real-time BTV surveillance and facilitates timely outbreak containment in resource-constrained agricultural and veterinary settings.